Chemical constituents of the soft corals Sinularia vanderlandi and Sinularia gravis from the coast of Madagascar. Issue 3 (2nd December 2015) - Rahelivao, Marie Pascaline; Gruner, Margit; Lübken, Tilo; Islamov, Daut; Kataeva, Olga; Andriamanantoanina, Hanta; Bauer, Ingmar; Knölker, Hans-Joachim
Abstract : The Madagascan soft corals S. vanderlandi and S. gravis provided five new natural products: vanderlandin (1 ), gravilin (2 ), the monoalkylmonoacylglycerol3, the dihomoditerpenoid ketone4, and isodecaryiol (5 ). Abstract : The crude extracts of the Madagascan soft corals Sinularia vanderlandi and Sinularia gravis (Alcyoniidae) showed activity against Plasmodium falciparum which led us to study their chemical constituents. The new cadinane-type sesquiterpenoid vanderlandin (1 ) has been obtained from S. vanderlandi along with 24-methylenecholesterol (2 ). Four new compounds, the spatane-type diterpenoid gravilin (3 ), the monoalkylmonoacylglycerol4, the dihomoditerpenoid ketone5, and isodecaryiol (9 ), along with the three known compounds (+)-( S )-geranyllinalool (6 ), (−)-( R )-nephthenol (7 ), and 11, 12-epoxysarcophytol A (8 ) have been isolated from the methanol extract of S. gravis . The structures were elucidated based on extensive spectroscopic methods, in particular various 2D NMR techniques. The structure of isodecaryiol (9 ) including its absolute configuration could be confirmed by X-ray diffraction.